Histórias que os militares contam: do golpe de 1964 aos primeiros anos da ditadura civil-militar no Brasil - Michel Goulart da Silva (Nuevo mundo - Mundos Nuevos, 2010)
This work has as object to argue articles and books concerning the blow of 1964 and the dictatorship civilian-military man, written for civilians and military and published by the publishing company Biblioteca do Exército (BIBLIEX). Some books launched for this publishing company and articles of the “Magazine of the Army” and “the National defence” are analyzed, published between 2003 and 2008, that they argue or they tell events related to the blow or to the dictatorial period. The theoretical bases are investigated that guide these historiographies versions, facing this speech as manifestations of thought conservative gifts today in the Armed Forces. In these versions of history, that take as starting point the elements of the historiography and propagating elaborated by the military and spread out during the proper dictatorial regime, the intervention of the Armed Forces would have been basic, therefore the military, considering themselves it parcel more good prepared of the elites in the conduction of the national interests, would have established again the public order in 1964. For this mentality conservative, the deriving intellectuals and politicians of the resistance to the dictatorship would use a speech with democratic elements today to occult its coup-minded nature, constructing what one of the military historians called “great lie”.